Nutritive value of Pleurotus ostreatus (Jacq.) P. Kumm. grown on some cellulosic residues - Akyüz, Mehmet; İnci, Şule; Kırbağ, Sevda (My University, 2021)
In this study, the effects of different cellulosic wastes on the nutritional values of Pleurotus ostreatus (Jacq.) P. Kumm. were investigated. Dry matter, moisture, protein, fat and ash contents of P. ostreatus were analyzed according to AOAC methods. Crude protein and fat contents were determined by the Kjeldahl method and Soxhlet extraction, using ether as a solvent, respectively. Chemical composition of P. ostreatus such as dry matter, moisture, crude protein, fat and organic matter were 93.5-93.7%, 6.3-6.5%, 25.2-33.5%, 1.7-2.5%, 5.3-9.7% and 84.0-88.2% of dry weight, respectvely. There were no significant differences in dry matter and moisture content of P. ostreatus grown on various local residues (p>0.05), but changeable in other nutrient composition (p<0.05). Crude protein, ash, fat and organic matter varied significantly, the lowest protein content was obtained from WS (25.2%), whereas the highest was obtained in the mixture of MS-WS (1:1) (33.5%) and MS-PP (1:1) (33.3%). P. ostreatus is highly valued as a good source of protein (25-33%), but low in fat (1.7-2.5%). It was observed that the type of substrate used for cultivation of P. ostreatus could influence the crude protein content of the fruit bodies.
Keywords: Biyoloji; Mantar Bilimi; Gıda Bilimi ve Teknolojisi